FUNCTIONAL OUTCOMES OF PERONEUS LONGUS TENDON AUTOGRAFT ARTHROSCOPIC RESTORATION OF AN ANTERIOR CRUCIATE LIGAMENT TEAR - RAZZAQUE, MA; HAIDER, MI; ZAHID, M; REHMAN, MU (Biological and Clinical Sciences Research Journal, 2022)
The study was conducted to assess the functional outcome of arthroscopic reconstruction of anterior cruciate ligament tear by using peroneus longus tendon autograft. A prospective study was conducted in the Orthopaedics Department of Bakhtawar Amin Memorial Trust, Multan from 22 June 2021-22 June 2022. A total of 24 patients from the out-patient department were included in the study. Patients were clinically examined, and MRI was performed to confirm the presence of tear. Arthroscopic reconstruction was done. IKDC was used to assess the final outcome after 6 months, MRC was used to evaluate ankle stability with normal side as control. IKDC was normal in 22 patients (91.6%) and abnormal in only 2 patients (20%). The average IKDC score was 82.44. Lachman test showed normal results in 17 (70.8%)patients, 1+ laxity in 4 (16.6%), 2+laxity in (8.3%) and 3+laxity in 1 (4.1%)patient. 14 (58.3%) patients had negative pivot shift and 10 (41.6%)had positive glide. Peroneus longus tendon autograft is an effective option for anterior cruciate ligament reconstruction with less complications and maintains ankle function.